'Positive' Gentrification, Social Control and the 'Right to the City' in Mixed-Income Communities: Uses and Expectations of Space and Place - Chaskin, Robert J.; Joseph, Mark L. (International journal of urban and regional research, 2013)
Public policies supporting market‐oriented strategies to develop mixed‐income communities have become ascendant in the United States and a number of other countries around the world. Although framed as addressing both market goals of revitalization and social goals of poverty deconcentration and inclusion, these efforts at ‘positive gentrification’ also generate a set of fundamental tensions — between integration and exclusion, use value and exchange value, appropriation and control, poverty and development — that play out in particular concrete ways on the ground. Drawing on social control theory and the ‘right to the city’ framework of Henri Lefebvre, this article interrogates these tensions as they become manifest in three mixed‐income communities being developed to replace public housing complexes in Chicago, focusing particularly on responses to competing expectations regarding the use of space and appropriate normative behavior, and to the negotiation of these expectations in thecontext of arguments about safety, order, what constitutes ‘public’ space, and the nature and extent of rights to use that space in daily life. Résumé Les politiques publiques favorables aux stratégies de marché pour constituer des communautés à revenus mixtes se propagent aux États‐Unis et dans plusieurs autres pays du monde. Conçues pour répondre à la fois à des objectifs de revitalisation associés au marché et à des objectifs sociaux de déconcentration de la pauvreté et d’inclusion, ces projets de ‘gentrification positive’ génèrent toutefois en ensemble de tensions élémentaires qui s’exercent concrètement sur le terrain (entre intégration et exclusion, valeur d’usage et valeur d’échange, appropriation et contrôle, pauvreté et développement). S’appuyant sur la théorie de la régulation sociale et sur le cadre du ‘droit à la ville’ d’Henri Lefebvre, l’article revient sur les tensions manifestées dans trois communautés à revenus mixtes de Chicago issues du réaménagement de complexes de logements sociaux. Il s’intéresse notamment aux réactions face aux attentes concurrentes quant à l’utilisation de l’espace et à un comportement normatif approprié, et face à la négociation de ces attentes dans un contexte antagoniste sur la sécurité, sur l’ordre, sur ce qui constitue l’espace ‘public’ ainsi que sur la nature et la portée des droits d’utilisation de cet espace au quotidien.